Una panoramica delle strategie di conservazione di opere d’arte digitale - Foti, Michele (Umanistica Digitale, 2018)
This text presents a guide to long-term conservation strategies for digital artwork. In addition to a brief presentation of each strategy mentioned in the literature on the subject, the reader will find a first approach to the main problems and bibliographical references to technical discussions. The consulted studies speak of a series of strategies among which museum employees and conservation professionals must choose on a case-by-case basis depending on the nature of the work. In fact, digital art works have characteristics (the physical components, the architecture of computer programs and the communicative and interactive aspects) that are extremely multiform and variable during their life cycle. The examples of works collected from the bibliography represent this fluid scenario. The computer allows the creation of new artistic languages, new forms and new aesthetics (such as virtual or augmented reality) which undermine conservative practices and principles linked to the preservation of material objects. Digital art is a type of conceptual, ephemeral and procedural art and it presents similarities with the conservative issues of contemporary art. Added to this are problems related to the use of computer networks, the miniaturization of physical components (hardware) and the extreme volatility of instructions (software) in computer language. The latter are given by the programmer/artist who often leaves his "mark" within them. Because operating system, computers and storage media have a short life cycle and are rapidly replaced by research and market innovations, digital works remain behind and, without any conservation measure, are condemned to illegibility in a few years. The literature on the subject privileges the conservation of the intangible and conceptual components of the artistic product compared to the physical and technological ones. The latter quickly become obsolete and may (must) be replaced or adapted to the context over the long term.